Managerial Ownership And Dividend Policy As Determinants of Company Value in Food and Bevergae Companies on the Indonesia Stock Exchange in 2019-2023 - Rahma, Audrey Dwi; Fitrios, Ruhul (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to test and analyze the influence of managerial ownership and dividend policy on company value. Methodology: This quantitative study uses a documentation method by collecting secondary data obtained from financial reports and annual reports of food and beverage companies from 2019-2023. The data analysis technique in this study uses descriptive statistical analysis, classical assumption tests, multiple linear regression tests, determination tests and partial tests processed using SPSS 27. Results: The t-test results indicate that managerial ownership and dividend policy have a significant partial effect on firm value. The R2 value in this study is 28.7%, which suggests that managerial ownership and dividend policy can explain the company’s value by 28.7%. Findings: Partially, managerial ownership and dividend policy affect company value. Novelty and Originality: This study uses the period 2019-2023 to examine the impact of the pandemic and the long-term impact of managerial ownership and dividend policy on company value after the pandemic. The sample in this study is more specific, namely, manufacturing companies in the food and beverage subsector. Conclusion: Based on research results, increasing company value can be done by increasing managerial ownership and dividend policy. Type of Paper: Research Article